2010
DOI: 10.1158/1078-0432.ccr-09-1456
|View full text |Cite
|
Sign up to set email alerts
|

PEA-15 Inhibits Tumorigenesis in an MDA-MB-468 Triple-Negative Breast Cancer Xenograft Model through Increased Cytoplasmic Localization of Activated Extracellular Signal-Regulated Kinase

Abstract: Purpose: To determine the role of PEA-15 in breast cancer. Experimental Design: A reverse-phase protein array was used to measure PEA-15 expression levels in 320 human breast cancers; these levels were correlated with clinical and tumor characteristics. PEA-15 was overexpressed by an adenovirus vector or by stably expressing PEA-15 in different breast cancer cell lines. The effects on breast cancer cell survival and on the downstream apoptotic signaling pathway were measured in terms of cell proliferation (try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 23 publications
5
36
0
Order By: Relevance
“…This finding is consistent with recent reports regarding the role of PEA-15 in activating cell death in breast cancer cells (Bartholomeusz et al, 2010). (Bartholomeusz et al, 2010). We discovered that the function of PEA-15 in mediating G129R-induced autophagy requires stabilization of the protein.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is consistent with recent reports regarding the role of PEA-15 in activating cell death in breast cancer cells (Bartholomeusz et al, 2010). (Bartholomeusz et al, 2010). We discovered that the function of PEA-15 in mediating G129R-induced autophagy requires stabilization of the protein.…”
Section: Discussionsupporting
confidence: 94%
“…The PEA-15 siRNA (ggaagacauccccagcgaatt) was described previously (Bartholomeusz et al, 2010). Adenoviral PEA-15 (Ad.PEA-15) was constructed by inserting PEA-15 cDNA into the adenoviral vector pAdTrack-CMV (He et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, whereas we were evaluating the effect of PEA15 on RAS-mediated transformation, the previous study was assessing the effect of PEA15 on RAS-transformed cells. Consistent with our results, several previous studies have shown that expression of PEA15 blocks tumor cell growth (46)(47)(48).…”
Section: Discussionsupporting
confidence: 93%
“…The PEA-15 siRNA (ggaagacauccccagcgaatt) was described previously (15). The EGFP-LC3 plasmid was derived from Addgene 11546(16).…”
Section: Methodsmentioning
confidence: 99%